RESEARCH ON APPLICATIONS OF CONTINUOUS IMPROVEMENT IN MANUFACTURING COMPANIES - Chengqi, Quan; Waworuntu, Stephanus Remond (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The ability to continuous improvement is part of an enterprise's core competitiveness. Only by continuous improvement can we better adapt to market changes and social progress and development. This study focuses on the problems of inventory backlog and low production efficiency faced by SZ Company, and deeply analyzes its root causes: inaccurate market demand forecasts, excess inventory caused by batch production mode, time differences between processes and imbalanced production capacity, etc. These problems not only increase capital occupation, but also cover up the deep-seated problems of the production system. In order to solve the above problems, this paper adopts a qualitative analysis method, applies the theory of Toyota Production System continuous improvement, and combines the successful experience of Mazak iSMART Factory project to propose a series of continuous improvement measures based on advanced technologies such as IoT , big data, and AI. By optimizing market demand forecasts and production plans, improving batch production modes, solving time differences and imbalanced production capacity between processes, improving employee skills and production efficiency, and realizing visualization and continuous improvement of the production process. This paper to provide SZ Company with a practical and feasible continuous improvement path combining the latest technology. Continuous improvement is solved the problems of high inventory and low production efficiency. It will help SZ Company significantly improve production efficiency, reduce operating costs, enhance market competitiveness, and ultimately achieve sustainable development and transformation and upgrading